Pengaruh Pemanfaatan Buku KIA terhadap Pengetahuan Ibu Hamil tentang Perawatan Kehamilan di Puskesmas Klakah Kabupaten Lumajang - Aminatus Zahro; Farianingsih Farianingsih; Homsiatur Rohmatin (NHM PRESS, 2023)
Maternal and child health book (MCH handbook) is a book that contains records of maternal health from pregnant women, mothers giving birth to postpartum mothers, and contains records of children's health, from newborns to children aged 6 years. One of the impacts of the poor use of MCH handbooks is the low knowledge of pregnant women about prenatal care, starting from the absence of pregnancy complications detected by health workers, due to not all pregnant women who make the first antenatal care visit continue until the 4th visit in the 3rd quarter (not according to standard). This study aims to determine the effect of the use of the MCH book on the knowledge of pregnant women about pregnancy care at the Klakah Health Center. This study is an analytic observational study with a cross sectional approach. The population in this study were pregnant women in the working area of the Klakah Health Center, Lumajang Regency, namely 793 people, with a sample of 89 people. The data was obtained by asking questions to respondents using a questionnaire. The results of this study showed that of the 62 pregnant women who used the MCH handbook, 36 people had good knowledge about pregnancy care, and 26 people had sufficient knowledge. Meanwhile, of the 27 pregnant women who did not use the MCH handbook, 4 had sufficient knowledge about pregnancy care and 23 had less knowledge. And after the statistical test was carried out, it was found that there was a significant effect between the use of the MCH Handbook on the Knowledge of Pregnant Women About Pregnancy Care. It is hoped that the public health center will be able to improve communication, information, and education (KIE) about the use of MCH books to the public, especially pregnant women, so that the knowledge and attitudes of mothers will also increase.